IRF (INITIATION-RESPONSE-FEEDBACK) ON CLASSROOM INTERACTION FOR COMPUTER STUDENTS IN SMK 1 YAPIM MEDAN - Shilvia Pratiwi; Dra. Meisuri, M.A.,; Nora Ronita Dewi, S.Pd., S.S., M.Hum. (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
This study was about IRF (Initiation-Response-Feedback) On Classroom Interaction For Computer Students in SMK 1 Yapim Medan. The aim of this study were to state clearly the objectives of the study in relation of the problems posed. The objective was to describe how the pattern of IRF in the classroom interaction for computer students. This research used qualitative research. The data were collected in three ways by observing by video recording, interviewing and questionnaire. The data was analyzed based on Sinclair and Coulthard theory (1975). The result of this study were the following (1) The language used by the teacher and the students in the classroom interaction was not balance. Both teacher and students used bahasa for 70% and the rest 30% for English. (2) There was the lowest pattern responded by student. It had 20% responses given to the students because the students made many mistakes in pronouncing some words when they read the text. The teacher feedback was the dominat pattern in the classroom interaction rather than initiation. It is suggested to English teacher especially for English teacher who is teaching computer students to improve students English by by having practice and supporting them to be brave to speak English.